Kepemimpinan Perempuan di Ranah Lokal: Analisis Kepemimpinan Gubernur Sherly Tjoanda di Provinsi Maluku Utara - Taufiqah Alifah Khairunisa; Rahma Dani Nuraulia; Ika Arinia Indriyany (Sociale : Journal of Social and Political Sciences, 2026)
This study examines women’s leadership in local politics through an analysis of Sherly Tjoanda as Governor of North Maluku Province using a transformational leadership perspective. The study is grounded in the low representation of women in local politics and the persistent dominance of patriarchal culture within political structures. The objective of this research is to understand the practices of women’s leadership and how such leadership is implemented within the context of regional governance. This study employs a descriptive qualitative method with a case study approach, utilizing primary and secondary data obtained from official documents, media sources, and academic literature. The findings reveal that Sherly Tjoanda’s leadership reflects key dimensions of transformational leadership, including inclusive political communication, the use of digital media, and direct engagement with communities to capture public aspirations. Her leadership is also demonstrated through responsive public policies in education, healthcare, and regional economic development. Furthermore, her leadership approach strengthens public trust through transparency, community participation, and empathetic governance. However, women’s leadership continues to face structural challenges, such as patriarchal culture, gender stereotypes, and limited access within political institutions. This study concludes that transformational women’s leadership plays a significant role in strengthening a more inclusive, participatory, and responsive local democracy.